(untitled) (Journal of the Management Sciences, 2024)
This research focuses on the impact of fuel subsidy removal on cooperative business performance in Imo state, Nigeria. It examines the effects of fuel subsidy removal on cooperative members’ income and input supply. The research investigates the intricate relationship between fuel subsidy policies and the operational dynamics of agricultural cooperatives input supply and members’ income performance. The study used survey research methodology, collecting data from cooperative societies in Ehime Mbano local government area. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with members and leaders of selected agricultural cooperatives in Imo State. The area of the study is Ehime Mbano local government area of Imo state. Ehime Mbano is a Local Government Area of Imo State. The population of selected agricultural cooperative societies are total membership strength of 2,180. A sample size 338 derived using Taro Yamani formula. Descriptive statistics such as frequency distribution, means and percentages was used to analyze the data obtained to address the objectives of the study. Also inferential statistics, such as one sample f-test and regression was employed to address the research questions and to test the promulgated hypotheses. The findings reveal that fuel subsidy removal has significantly affected both cooperative farm input supply and member’s income. The results support the notion that removing fuel subsidies all at once leads to short-term price increases, impacting cooperative businesses.